Multidrug Resistance Regulators MarA, SoxS, Rob, and RamA Repress Flagellar Gene Expression and Motility in Salmonella enterica Serovar Typhimurium - Thota, Srinivas S.; Chubiz, Lon M. (Journal of bacteriology, 2019)
The mar-sox-rob regulon is a large and highly conserved stress response network in the Enterobacteriaceae family. Although it is well characterized in E. coli , the extent of this regulon in related species is unclear. Here, the control of costly flagellar gene expression is connected to the mar-sox-rob regulon of S . Typhimurium, contrasting with the E. coli regulon model. These findings demonstrate the flexibility of the mar-sox-rob regulon to accommodate novel regulatory targets, and they provide evidence for its broader regulatory role within this family of diverse bacteria. Production of flagella is costly and subject to global multilayered regulation, which is reflected in the hierarchical control of flagellar production in many bacterial species. For Salmonella enterica serovar Typhimurium and its relatives, global regulation of flagellar production primarily occurs through the control of flhDC transcription and mRNA translation. In this study, the roles of the homologous multidrug resistance regulators MarA, SoxS, Rob, and RamA (constituting the mar-sox-rob regulon in S . Typhimurium) in regulating flagellar gene expression were explored. Each of these regulators was found to inhibit flagellar gene expression, production of flagella, and motility. To different degrees, repression via these transcription factors occurred through direct interactions with the flhDC promoter, particularly for MarA and Rob. Additionally, SoxS repressed flagellar gene expression via a posttranscriptional pathway, reducing flhDC translation. The roles of these transcription factors in reducing motility in the presence of salicylic acid were also elucidated, adding a genetic regulatory element to the response of S . Typhimurium to this well-characterized chemorepellent. Integration of flagellar gene expression into the mar-sox-rob regulon in S . Typhimurium contrasts with findings for closely related species such as Escherichia coli , providing an example of plasticity in the mar-sox-rob regulon throughout the Enterobacteriaceae family. IMPORTANCE The mar-sox-rob regulon is a large and highly conserved stress response network in the Enterobacteriaceae family. Although it is well characterized in E. coli , the extent of this regulon in related species is unclear. Here, the control of costly flagellar gene expression is connected to the mar-sox-rob regulon of S . Typhimurium, contrasting with the E. coli regulon model. These findings demonstrate the flexibility of the mar-sox-rob regulon to accommodate novel regulatory targets, and they provide evidence for its broader regulatory role within this family of diverse bacteria.